Coverage criteria for UML state chart diagram in model-based testing - Salman, Yasir Dawood; Hashim, Nor Laily; Md Rejab, Mawarny; Romli, Rohaida; Mohd, Haslina (Universiti Teknikal Malaysia Melaka, 2017)
Software testing is a necessary and essential part of the software quality process and plays a major role in detecting errors in systems. To improve the effectiveness of test case generation during software testing, and with the growing adoption of UML by software developers and researchers, many studies have focused on the automation of test case generation from UML diagrams. One of these diagrams is the UML state chart diagram. These test cases are generally generated to achieve certain coverage criteria. However, combinations of multiple criteria are required to achieve better coverage. Different studies use various number and type of coverage criteria in their methods and approaches. This paper reviews previous studies to present the most practical coverage criteria combinations for UML state chart diagram, including all-states, all-transitions, all-transition-pairs and all-loop-free-paths coverage. A special calculation is necessary to determine the coverage percentage of the proposed coverage criteria. This paper presents a calculation method to achieve this goal with an example is applied to a UML state chart diagram. This finding would be beneficial in the area of automatic test case generating for model-based testing and especially in the UML state chart diagram.